Moral and Instrumental Norms in Food Risk Communication - Modin, Peter G.; Hansson, Sven Ove (2011)
The major normative recommendations in the literature on food risk communication can be summarized in the form of seven practical principles for such communication: (1) Be honest and open. (2) Disclose incentives and conflicts of interest. (3) Take all available relevant knowledge into consideration. (4) When possible, quantify risks. (5) Describe and explain uncertainties. (6) Take all the public’s concerns into account. (7) Take the rights of individuals and groups seriously. We show that each of these proposed principles can be justified both in terms of more fundamental ethical principles and instrumentally in terms of the communicating agent’s self-interest. The mechanisms of this concordance of justifications are discussed. It is argued that the concordance is specific for areas such as food risks in which agents such as companies and public authorities are highly dependent on the public’s trust and confidence. The implications of these findings both for moral philosophy and for practical food risk communication are discussed.
Keywords: principlism; Applied Ethics; instrumental norms; Risk communication; Food Ethics